Penerapan Kurikulum PHI (Pendidikan Holistik Integral) dalam Pembelajaran di SMPIT LHI Yogyakarta - Sri Syafa'ati (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This study aims to determite the application of the PHI curriculum in learning, as well as knowing the obstacles encountered and the strategies undertaken to overcome these obstacles in SMP IT Yogyakarta. The results of the study are; 1) The PHI curriculum is applied in every learning in SMPIT LHI Yogyakarta through the PBL (Project Based Learning) method, as well as being used as name of the subject, in which the main themes are based on the basic concepts, principles and models of Integral Holistic education. 2) Obtacles experienced namely; a) difficulties in translating books, b) there are no steps or guidelines in its application, c) not all teachers have educational background in PAI, d) it is still difficult to integrate public subjects with PAI, and e) there is no suitable book when applying PHI in learning. 3) Strategies undertaken by the school in overcoming various obstacles are; a) forming curriculum teams dan drafter, b) every odd semester there is always refreshing and upgrading/training related to the PHI curriculum, c) teachers look for various sources to be able to integrate in each subject, hold seminars and meetings regarding the introduction of the PHI curriculum, and d) looking at the same time making from various literacy sources to be used as material in teaching